What are the benefits of using questioning to scaffold critical thinking skills in literacy in the kindergarten classroom? - Lee, Julie Christine (My University, 2013)
The purpose of this action research study is to examine ways to teach, model, guide and scaffold critical thinking mainly through questioning, so that all levels of learners can be immersed and engaged in meaningful, purposeful comprehension work. Can young children learn to think critically and ask questions about what they read? Can they synthesize elements of a story, retaining information to complete a thought at the end of the story? The author used teacher action research to investigate these questions and explore the effects of scaffolding critical thinking while working with sixteen kindergarten students and their parents. The impact of parent involvement has a sound research base attesting to the many potential benefits it can offer in education; however, kindergarten students' ability to think critically and synthesize in conjunction with parental involvement has only recently been investigated. This research presents a model of scaffolding critical thinking skills with kindergarten children, while at the same time increasing the confidence level and literacy skills of the parents. The author created pre and post questionnaires for parents to complete. The pre questionnaire was designed to assess: a) behaviors the parent and child engage in during home reading, b) parents' views on the importance of reading, and c) parents' reading habits. The post questionnaire was designed to detect and document reading behaviors that continued or changed during the course of the study. The sixteen students in this study were also given questionnaires before and after the unit of study. Most students' instructional levels increased by one level (Benchmark Assessment System by Fountas and Pinnell) and in some instances two levels over the course of the study. Gains were made during the synthesis unit of study as well. Parents reported a greater appreciation of the importance of reading in their lives and their child's life. Results indicate that the largest gains were made in the students' understanding of questioning, including what a question is, and how to implement questioning and synthesis strategies.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 54 leaves. Includes bibliographical references (leaves 34-36).
Keywords: Critical thinking; Critical thinking skills; Questioning; Reading (Kindergarten); Reading; Literacy